Optimalisasi Kinerja Alat Torefikasi pada Proses Pembuatan Biochar dari Limbah Jengkok Tembakau - Susanto, Susanto; Indah Wana, Yaniar Lisa; Iskandar, Taufik; Abrina Anggraini, Sinar Perbawani (Prosiding Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur)
The amount of tobacco waste produced by the cigarette industry reaches 20 tons/day has the potential to pollute the environment if it is not processed first. Tobacco waste content is dangerous because there is heavy Arsenic metal that not in accordance with environmental quality standards, which is 24.19 ppm. Therefore, further technological and waste management approaches need to be taken to become a product that is beneficial and safe for the environment. The processing that can be done is to convert tobacco waste into biochar (Bio-Charcoal) using a Torefication equipment. In the Torefication process there are factors that influence, including temperature and time treatment. Determination of the right temperature and time will determine the quality of biochar produced. The purpose of this reseach was to determine the optimal temperature and time in achieving the best performance of Torefication equipment in the biochar production process from tobacco waste. Changing variables used were temperature (400oC, 450oC, 500oC, 550oC and 600oC) and time (30 minutes, 35 minutes, 40 minutes). The research parameters are % yield, missing components and equipment performance. The result of this reseach showed that the highest and lowest of % yield is 58.37% and 26.27%, the highest and lowest missing components are 73.73% and 41.63% and the highest and lowest equipment performance is 58.2 g/(jam.m) and 19.7 g/(jam.m). Based on statistical analysis the optimal temperature and time is at 450oC and 30 minutes.